Minimum-Perimeter Lattice Animals and the Constant-Isomer Conjecture - Barequet, Gill; Ben-Shachar, Gil (The Electronic Journal of Combinatorics, 2022)
We consider minimum-perimeter lattice animals, providing a set of conditions which are sufficient for a lattice to have the property that inflating all minimum-perimeter animals of a certain size yields (without repetitions) all minimum-perimeter animals of a new, larger size. We demonstrate this result on the two-dimensional square and hexagonal lattices. In addition, we characterize the sizes of minimum-perimeter animals on these lattices that are not created by inflating members of another set of minimum-perimeter animals.